Economic Feasibility of Thermal Energy Storage Systems in Saudi Arabian Schools: A Case Study - Badr Habeebullah; Rahim Jassim; Nedim Turkmen; Ahmad Bokhary; Majed Alhazmy (Engineering Research: Perspectives on Recent Advances Vol. 3, 2025)
Air conditioning in houses, office buildings and schools consumes a high portion of the generated electricity in Saudi Arabia. The high consumption rates encourage the authorities to work on both increasing the energy generating rates and reducing the demand. This paper presents a study of the economic opportunities afforded by installing an ice storage system in existing air conditioning plants of a school in Jeddah, Saudi Arabia. In this paper, the assumptions are i) a fixed interest rate of 10%, ii) a tenure of 10 years and iii) an estimated operational tariff structure depending on both the number of operating hours and the ambient temperature. The study examines both full and partial load storage scenarios and then calculates the effect of various pricing tariffs on cost optimization. New school buildings in Jeddah are constructed according to a standard plan called Mubassat Modon. Schools are normally built as a complex of three identical buildings. Each school contains twenty-five classrooms, two offices, two labs, an open area, and a library distributed on three floors. The analysis in this study uses Energyplus to perform the cooling load calculations for the school’s three floors. The results show that the current fixed electricity tariff rate of 0.0267/kWh is not economically feasible. Combining both energy storage and an incentive time-structured rate shows reasonable daily bill savings. For a base tariff of 0.07/kWh during daytime operation and 0.0267/kWh for the off-peak period, savings of 33/d and 73.36/d are achievable for full load storage and partial load scenarios, respectively. These savings will increase to 159/d for full load storage and 124.06/d for partial load storage after 10 years. Combining energy storage and an incentive time structured rate showed reasonable daily bill savings.